PERANAN PENGENDALIAN INTERNAL DALAM MENGANTISIPASI KECENDERUNGAN KECURANGAN PENGELOLAAN KEUANGAN DESA - Rusli Amrul; Herawati Khotmi (Valid: Jurnal Ilmiah, 2016)
In this research, wanted to know the role of internal control in anticipation of the tendency of the financial fraud in 14 villages in the Kecamatan Gerung of Kabupaten Lombok Barat terms of Environmental Control, Risk Control, Control Activities, Information and communication and monitoring. The research method used descriptive qualitative method. Source data from this study are primary data. Place of research conducted in several villages in the district Gerung the Village Banyu Urip, Dasan Geres, Babussalam, Dasan Tapen, Beleke, Kebun Ayu, Gapuk, Suka Makmur, Tepos, South Gerung, North Gerung, Mesanggok, Giri Tembesi and Taman Ayu. The technique of collecting data through interviews and questionnaire. The analysis technique used in this study includes various phases that start share questionnaire, collect, categorize answers, perform final scoring and classify the achievements of respondents. From research conducted inferential control environment reached 77.50%, which means achievement role in internal control, risk control reached 91.67% categorized as very instrumental in internal control, Control activities to the achievement of 59.46 categorized quite a role in internal control, information and communication have a 92.67% performance categorized as very instrumental in internal control, performance monitoring has 78.29% categorized role in internal control and together the five components has 78% outcomes, 29% is the category has a role in internal control. And suggested that there should be standards of ethics and behaviour, there is an internal examiner, there is segregation of duties and responsibilities and there is a safe place to store money is to avoid financial abuse villages